Проблемы, перспективы и основные направления развития экологически чистых источников электроэнергии в Украине - Шевченко, Валентина Владимировна; Лизан, Игорь Ярославович (Украинская инженерно-педагогическая академия, 2011)
Определены проблемы создания, внедрения в силовую энергетику и эксплуатации экологически чистых источников электроэнергии. Рассмотрено современное состояние и перспективы использования возобновляемых источников энергии (ветроэнергетика, гидроэнергетика, перспективные типы современных генераторов – с магнитоэлектрическим возбуждением, с использованием высокотемпературных сверхпроводников).

Problems of creation, introduction in power and operation of non-polluting sources of the electric power are defined. The current state and prospects of use of renewed energy sources (windpower, water-power engineering, perspective types of modern generators – with magnetoelectric excitation, with use of high-temperature superconductors) is considered.
Problems, prospects and the basic directions developments of non-polluting sources the electric power in Ukraine
Keywords: электроэнергетика; ветроэнергетика; безопасность экологическая; энергосбережение; electric power industry; windpower; ecological safety; power savings